2017
DOI: 10.17409/kpt.60095
|View full text |Cite
|
Sign up to set email alerts
|

Suomalainen kulttuuriosallistuminen ja eriarvoisuus: ei-osallistujien jäljillä

Abstract: Finnish society is often considered culturally homogeneous, and an aura of middle-class spirit is claimed to label the Finns’ cultural taste and cultural participation. However, it is a well-demonstrated fact that both are intrinsically linked to structural factors like income and social status. The aim of this article is to figure out how Finnish cultural non-participation patterns are distributed in the population and to explore how the leisure time of the non-participants of (highbrow) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
1
0
10
Order By: Relevance
“…At the same time, they are a large and relatively heterogeneous group (Chan and Goldthorpe, 2007b; Gayo, 2017). Earlier (Heikkilä, 2017), I have found that cultural non-participation can entail resentment and hostility toward the established order and its accredited lifestyles altogether: in this sense, my research could reveal underlying symbolic struggles of culturally non-active popular classes, totally disregarded by Bourdieu (1984) and still not discussed enough in contemporary sociology. While we know that cultural non-participation tends to be linked to certain recurrent factors such as low education and low class position, it can be expected that on the individual level there are different orientations of participation or non-participation.…”
Section: Methodsmentioning
confidence: 71%
“…At the same time, they are a large and relatively heterogeneous group (Chan and Goldthorpe, 2007b; Gayo, 2017). Earlier (Heikkilä, 2017), I have found that cultural non-participation can entail resentment and hostility toward the established order and its accredited lifestyles altogether: in this sense, my research could reveal underlying symbolic struggles of culturally non-active popular classes, totally disregarded by Bourdieu (1984) and still not discussed enough in contemporary sociology. While we know that cultural non-participation tends to be linked to certain recurrent factors such as low education and low class position, it can be expected that on the individual level there are different orientations of participation or non-participation.…”
Section: Methodsmentioning
confidence: 71%
“…(Yli Jokipii 1996;Muranen 2011. ) Suomalaisessa maaseudun kylämaisemassa korostetaan luonnon moni muotoisuutta, maatalouden tuotantomaisemaa, talonpoikaista arkkiteh tuuria ja maiseman historiallisiin piirteisiin liittyviä arvoja (Luostarinen & YliViikari 1997;Raivo 1999, 84;Heikkilä 2000). Maaseudun elinkei norakenteen muutos, viljelyekosysteemien köyhtyminen ja rakennus kannan muutokset herättivät niin ympäristöhallinnon kuin kotiseutu aktiivit jo 1980luvulla toimiin perinteiseksi mielletyn maaseutumai seman muutoksen hallitsemiseksi.…”
Section: Maiseman Ja Urheilun Suhdeunclassified
“…Keskiluokkaisen kulutuskulttuurin normiston (esim. Heikkilä, 2016) hylkäävälle kertojalle on "ihan sama onks se hanhenmaksaa vai makkaraa", Lidlin kaljaa vai shampanjaa.…”
Section: Jääminenunclassified